Implicatures Generated from Non-Observances Maxim in The Interview of the Indonesian President - Adena, Tiara; Zuindra, Zuindra; Mulia, Hendra (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
The aims of this research are to (1) To find out the types of conversational implicatures (2) to describe how the implicature exist (to find out the types of non-observance maxim of cooperative principle) and (3) To find the purpose of generate implicature. This research was descriptive qualitative. The data of this research were the dialog in BBC News Indonesia’s Interview with Joko Widodo. To analyze the data in this research, the theory of implicature and the non-observance cooperative principle by Grice was employed. In the data analysis the researcher applied qualitative data method by Miles and Huberman (2014). The results of the research found there were 16 implicatures identified out of 18 of data in the dialogue, while the other 2 were general implicatures. Additionally, the researcher identified a lot of disregarded maxim forms. The most frequently disregarded maxim was the flouting of the maxim of quantity. Abstrak Tujuan dari penelitian ini adalah (1) Mengetahui jenis-jenis implikatur percakapan, (2) menjelaskan bagaimana implikatur tersebut muncul (untuk mengetahui jenis pelanggaran prinsip kerjasama non-observasi), dan (3) menemukan tujuan dari pembentukan implikatur. Data penelitian ini adalah percakapan dalam wawancara BBC News Indonesia dengan Joko Widodo. Untuk menganalisis data pada penelitian ini digunakan teori implikatur dan prinsip kerjasama non-observasi oleh Grice. Dalam analisis data, peneliti menerapkan metode data kualitatif oleh Miles dan Huberman (2014). Hasil penelitian menemukan bahwa terdapat 16 implikatur khusus yang diidentifikasi dari 18 data dalam percakapan, sedangkan 2 lainnya merupakan implikatur umum. Selain itu, peneliti mengidentifikasi banyak bentuk pelanggaran prinsip yang diabaikan. Prinsip yang paling sering dilanggar adalah pelanggaran prinsip kuantitas.